Intervention of Kusuma Milk-Shake Drink on Cervical Dilatation and Duration of Labor: Experience from Bengkulu, Indonesia - Dwie Yunita Baska; Elly Elly Wahyuni; Nispi Yulyana (Althea Medical Journal, 2023)
Background: Labor processes require energy consumption regulated by a complex nervous system and hormonal response. Thus, the intensity of maternal nutritional intake since pregnancy should be highly considered for physiological delivery. Nutrients that are high in energy and provide fast-decomposing glucose intake should be chosen by the mothers. Kusuma is a kind of drink made from dates, milk, and honey. This study aimed to analyze the effect of Kusuma milk-shake drink implementations on cervical dilatation and duration of labor.Methods: An experimental study was conducted by post-test only with a controlled group design, including 34 mothers with term pregnancy, which was intervention groups and controls. A completely randomized design in two different places was conducted. Data were analyzed using Shapiro-wilk, independent sample T-test, and Mann-Whitney. Results: There was a significant effect of Kusuma milk-shake implementation on cervical dilatation (p=0.000). The dilatation process was found to be 5.5 times faster, and the duration of labor (p=0.000) was observed to be 9.7 hours faster than the control group.Conclusions: Implementation of the Kusuma milk-shake has a significant effect on the acceleration of cervical dilation and the duration of labor. This research is expected to improve the quality of midwifery services as an effort to realize the concept of a Continuum of Obstetric Care.